2013
DOI: 10.1186/1824-7288-39-64
|View full text |Cite
|
Sign up to set email alerts
|

Refractory rheumatoid factor positive polyarthritis in a female adolescent already suffering from type 1 diabetes mellitus and Hashimoto’s thyroiditis successfully treated with etanercept

Abstract: Type 1 diabetes mellitus may be associated with many autoimmune diseases with the common autoimmune pathogenesis. We describe the case of a girl suffering from Type 1 diabetes mellitus and autoimmune Hashimoto's thyroiditis since the childhood and, due to the onset of Juvenile Idiopathic Arthritis during adolescence, for three years practiced therapy with an anti-TNF drug, etanercept . Currently her inflammatory markers are normal, arthritis is inactive and diabetes is well controlled. During the treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Although there are no other trials of TNF inhibitors for diabetes treatment, there are case reports of patients with autoimmune diabetes who experienced improved glycemic control and/or hypoglycemia after initiating treatment with etanercept [80, 81], adalimumab [8284], and infliximab [85], suggesting that the effects of etanercept on type 1 diabetes are generalizable to TNF inhibitors as a group. Of note, there are two reported cases of type 1 diabetes developing shortly after TNF inhibitors were started, raising the concern that TNF inhibitors were the cause [86, 87].…”
Section: Diabetes-specific Effects Of Rheumatologic Immune Modulatorsmentioning
confidence: 99%
“…Although there are no other trials of TNF inhibitors for diabetes treatment, there are case reports of patients with autoimmune diabetes who experienced improved glycemic control and/or hypoglycemia after initiating treatment with etanercept [80, 81], adalimumab [8284], and infliximab [85], suggesting that the effects of etanercept on type 1 diabetes are generalizable to TNF inhibitors as a group. Of note, there are two reported cases of type 1 diabetes developing shortly after TNF inhibitors were started, raising the concern that TNF inhibitors were the cause [86, 87].…”
Section: Diabetes-specific Effects Of Rheumatologic Immune Modulatorsmentioning
confidence: 99%
“…It can competitively combine with TNF-α and then block the combination of TNF-α and its receptor, resulting in inhibition of TNF-α activity (10). Several studies have demonstrated that etanercept is used to treat TNF-α-related diseases, such as rheumatoid arthritis (11), Crohn’s disease (12), ankylosing spondylitis (13), psoriasis (14), diabetes mellitus (15), Alzheimer disease (16) and cancers (17). Notably, increased level of TNF-α is found in patients with heart failure, and TNF-α has been proven to serve as a prognostic factor of heart failure (18).…”
Section: Introductionmentioning
confidence: 99%
“…The management of DM is a great challenge especially in adolescents ( 4 , 5 ). The adolescents with from type 1 DM are on the verge of being independent from their families but the disease hinders their relations with others ( 6 ). Nowadays one of the most significant health problems in developed as well as developing societies is increasing prevalence of DM, which puts financial burden on the affected families and the societies and causes psychologic problems for the patients and families.…”
Section: Introductionmentioning
confidence: 99%